A comparison of rolled, coarsely ground, and finely ground milo grain for fattening steer calves. - Cox, R.F.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Good to choice quality Hereford steer calves were used in this test. There were three lots, 10 head to a lot, all being fed the same except for the difference in grain preparation. The calves originated in the vicinity of Sonora, Texas. They were maintained on a roughage ration properly supplemented for about six weeks prior to starting on test on December 5, 1950. They were sprayed with B.H.C. for lice. At the start of the test, they were fed all of the sorghum silage they would clean up each day, 2 pounds of alfalfa hay and 1 ½ pounds of soybean oil meal pellets per head daily.
Keywords: Beef; Milo grain; Gain; Carcass grades